2019
DOI: 10.1111/sdi.12811
|View full text |Cite
|
Sign up to set email alerts
|

A swan song for Kt/Vurea

Abstract: Dialyzer clearance of urea multiplied by dialysis time and normalized for urea distribution volume (Kt/Vurea or simply Kt/V) has been used as an index of dialysis adequacy since more than 30 years. This article reviews the flaws of Kt/V, starting with a lack of proof of concept in three randomized controlled hard outcome trials (RCTs), and continuing with a long list of conditions where the concept of Kt/V was shown to be flawed. This information leaves little room for any conclusion other than that Kt/V, as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 195 publications
(230 reference statements)
0
20
0
Order By: Relevance
“…Urea level is currently used as the standard marker for dialysis adequacy and is obtained by calculation of clearance index Kt/V [ 46 ]. Nevertheless, Kt/V has several disadvantages: it is complex and tedious to calculate, it ignores the mass transfer between body compartments and across the plasma membrane, which has been shown to be important for the clearance of molecules, practical use of Kt/V requires adjustment for a rebound of the urea concentration due to the multi-compartmental nature of the body, the volume of water per weight of human body needed for Kt/V calculations depends on gender, body size, hydration status, etc [ 47 , 48 ]. Usually the most popular time of in-center HD is calculated theoretically, overlooking these important aspects, and most often, the safe time is selected as four hours [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Urea level is currently used as the standard marker for dialysis adequacy and is obtained by calculation of clearance index Kt/V [ 46 ]. Nevertheless, Kt/V has several disadvantages: it is complex and tedious to calculate, it ignores the mass transfer between body compartments and across the plasma membrane, which has been shown to be important for the clearance of molecules, practical use of Kt/V requires adjustment for a rebound of the urea concentration due to the multi-compartmental nature of the body, the volume of water per weight of human body needed for Kt/V calculations depends on gender, body size, hydration status, etc [ 47 , 48 ]. Usually the most popular time of in-center HD is calculated theoretically, overlooking these important aspects, and most often, the safe time is selected as four hours [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chief among these are its failure to measure middle molecule clearance and to meaningfully distinguish between the separate effects of time spent on dialysis and clearance, inaccuracy in select groups of patients (e.g., at the extremes of body mass index), lack of a standardized approach to measurement, and failure to address volume management. [5][6][7][8][9][10] Despite widespread recognition of the importance of delivering an adequate dialysis dose within the nephrology community and improvements over time in the provision of dialysis, mortality rates for patients on dialysis remain extremely high. Clinical trials in this area-which have been limited by inadequate power, reliance on surrogate markers, and failure to include outcome measures that matter to patients-have failed to show a clear and consistent benefit of increasing Kt/V above the minimum threshold level recommended in clinical practice guidelines or of increasing dialysis session length or frequency.…”
Section: O'harementioning
confidence: 99%
“…These findings suggest that the frequency and duration of therapy play a role beyond what is able to be evaluated by the conventional adequacy measurement of Kt/V. A recent review further highlighted 19 studies where dissociation between Kt/V and adequacy of dialysis, with differences in outcomes occurring despite groups having the same Kt/V, or groups with different Kt/V having similar outcomes 29 …”
Section: Alternative Hemodialysis Schedules and The Role Of Residual mentioning
confidence: 99%
“…A recent review further highlighted 19 studies where dissociation between Kt/V and adequacy of dialysis, with differences in outcomes occurring despite groups having the same Kt/V, or groups with different Kt/V having similar outcomes. 29 The Netherlands Cooperative Study on the Adequacy of Dialysis (NECOSAD) study looked at the impact of residual kidney function (RKF) on mortality and found that mortality was lower for patients with any degree of RKF compared to anuric patients, and that for patients who were not anuric, the amount of delivered dialysis, as measured via Kt/V, did not affect mortality. 30 Thus, an alternative dialysis schedule utilizing incremental HD, where incident dialysis patients who still maintained a high degree of RKF at the time of initiation may be adequately treated with only twice weekly dialysis, was proposed.…”
Section: Alternative Hemodialys Is Schedule S and The Role Of Re S Idual Kidne Y Fun C Tionmentioning
confidence: 99%